Quiet Quitting and Counterproductive Work Behavior: Evidence from a Cross-Sectional Study of Healthcare Professionals Across Organizational and Interpersonal Outcomes - Danijela Ilic; Violeta Domanovic; Marko Slavkovic (Healthcare, 2026)
Background/Objectives: Quiet quitting has become an increasingly prominent workplace phenomenon, particularly within healthcare organizations. Although previous research has primarily focused on the factors associated with its emergence, considerably less attention has been devoted to its relationships with undesirable workplace behaviors. This study examined the relationship between quiet quitting and selected forms of counterproductive work behavior among healthcare professionals. Methods: A cross-sectional study was conducted among healthcare professionals employed in public healthcare institutions in Central Serbia. Data were collected between February and March 2026 using a structured questionnaire. Quiet quitting was assessed using the Quiet Quitting Scale (QQS), while counterproductive work behavior was measured through selected dimensions of the Counterproductive Work Behavior Checklist (CWB-C). The data were analyzed using partial least squares structural equation modeling (PLS-SEM). Results: Quiet quitting was positively and statistically significantly associated with counterproductive work behavior directed toward the organization, counterproductive work behavior directed toward coworkers, and withdrawal behavior. The strongest relationship was observed for counterproductive work behavior directed toward coworkers. No statistically significant relationship was identified between quiet quitting and sabotage. Multigroup analysis indicated differences in several relationships across gender and age groups. Conclusions: The findings indicate that quiet quitting is associated with several forms of counterproductive work behavior in healthcare organizations. The differentiated pattern across organizational, interpersonal, withdrawal-related, and sabotage outcomes supports the view that quiet quitting and counterproductive work behavior are conceptually related but not equivalent.